De la intelligentsia de la Facultad de Derecho de la Universidad de Buenos Aires - Ortiz, Tulio (2012)
The role of universities in the formation of the leader classes in the foundational stages of a nation, and still later, has been studied from different points of view. The Faculty of Law of the University of Buenos Aires, consubstantial with the birth of the Nation from its inception, not only has formed fifteen presidents of Argentina, but also a great part of the leader class and social references, that, from different points, had, as denominator, the good of the society. In this chapter, we analyze some of the facets of this historical role, its men, ideas and fights because this book proposes to condense some relevant aspects of the contribution of the Faculty of Law of the University of Buenos Aires in Argentina?s history. The ideas, men and works of the Faculty of Law have accompanied the country since its inception and designed the modern Argentine state, in a great part. As area of creation and conformation of an influential intellectuality in the political power, or intelligentsia, the Faculty of Law of the University of Buenos Aires has traveled the almost two hundred years of the successive stages of the Argentine State. Our aim is that this work is a new contribution to be followed by others, destined to study our past, in the conviction of contributing to the recovery of the historical memory and the identity of our nation, in the Bicentenary of the Revolution of May.